-7y-42=-5(y+6)

Simple and best practice solution for -7y-42=-5(y+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7y-42=-5(y+6) equation:


Simplifying
-7y + -42 = -5(y + 6)

Reorder the terms:
-42 + -7y = -5(y + 6)

Reorder the terms:
-42 + -7y = -5(6 + y)
-42 + -7y = (6 * -5 + y * -5)
-42 + -7y = (-30 + -5y)

Solving
-42 + -7y = -30 + -5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '5y' to each side of the equation.
-42 + -7y + 5y = -30 + -5y + 5y

Combine like terms: -7y + 5y = -2y
-42 + -2y = -30 + -5y + 5y

Combine like terms: -5y + 5y = 0
-42 + -2y = -30 + 0
-42 + -2y = -30

Add '42' to each side of the equation.
-42 + 42 + -2y = -30 + 42

Combine like terms: -42 + 42 = 0
0 + -2y = -30 + 42
-2y = -30 + 42

Combine like terms: -30 + 42 = 12
-2y = 12

Divide each side by '-2'.
y = -6

Simplifying
y = -6

See similar equations:

| 3x+2y=456 | | -4(v+3)=7v+21 | | 2u+17=-5(u-9) | | -4(u+1)=5u+5 | | X^2dy+y^2dx= | | (2x+4)+(4x+2)=(6x+6) | | 17=3u+2 | | -3x+92=4x+1 | | -11=-8+r-3 | | -12=5x+8x | | 6(-1-7k)=-8(7-k) | | 8(9-2k)=9(1-k) | | 8x+38=6x+6240 | | -11(8m-6)=-2-7(12m-8) | | -23+6x=5x+2(5x+2) | | 8p+21=-3(-8p-7) | | -11=8+r-3 | | (12x-8)+(12x-8)=(22x-11) | | 2(5+5k)=4+8k | | 1d/10-12 | | 3-1/t-2/t^2=0 | | lx-2l=2x+1 | | f(x)=7x^2+4x-3 | | 0.05x-0.1x+0.6=0.04x+2.22 | | (8x-3)+(8x-3)=(10x+30) | | =29*4 | | 7700+1900+700+160= | | 0.05x-0.1x+0.6=0.04+2.22 | | 0.05-0.1x+0.6=0.04+2.22 | | =(81+162t^2+81t^4) | | =sqrt(81+162t^2+81t^4) | | 4.25E-19= |

Equations solver categories